Modelo de gestión por procesos y su efecto en la cultura organizacional de la gerencia de personal de la municipalidad provincial de Trujillo, 2014-2017 - Cortijo Villarroel, Carmen Esperanza (2017)
The objective of the present investigation is to analyze the effect of the process management model on the organizational culture of the personnel management of the Provincial Municipality of Trujillo during the period 2014 - 2017. The work is based on theories about the organizational culture and the management of processes, from which their determinants are deduced. According to the established theory our hypothesis is that: The process management model has an effect on the organizational culture of the personnel management of the Provincial Municipality of Trujillo. The study is a type of basic, non - experimental longitudinal and correlational research, in which the hypothetical - deductive method was used. To achieve the proposed objectives, an econometric estimation and economic evaluation was performed using a linear regression model using some of the variables mentioned in the theoretical framework. Finally, the findings obtained in the research show that the hypothesis is accepted; their respective coefficients having been found: 18.1 for the capacity management to cover the demand of users, 0.0482 for the management of the waiting time of the users and 0.56 for the management of the quality of the service.